PRESERVING THE BENEFITS OF THE HOLDING COMPANY. - Green, Paul M. (The Accounting Review, 1933)
Abstract The holding company may be defined as a company which holds a substantial interest in the stock of one or more corporations. Organizations have been established and are in operation at the present time which hold a minority interest in some one corporation, their investment in this company being a very small part of their total assets, as of March 1933. This is one extreme. The other is the giant corporation, the assets of which consist in entirety of the securities of other corporations. In the broad sense of the term, these are both holding companies and there may be found holding companies at each stage between these two extremes. The author attempts to distinguish between the pure holding company and the so-called parent company. Students of corporation finance generally agree that the pure holding company is one which owns no physical properties in its own name and operates none as an organization. Its function is one of holding securities in other corporations for the purpose of directing their activities. The parent company owns both physical properties and securities of other corporations. It has a two-fold purpose, that of operating its producing assets and controlling the properties of its subsidiaries through stock voting.